Postmortem Examination After Exposure to Radioactivity - Özsoy, Sait; Ortatatlı, Mesut; Emer, Özdeş; Tuğcu, Harun (The Bulletin of Legal Medicine, 2011)
Radioactivity is used for diagnostic and treatment purposes, but it can also be used in criminal activity. Further evaluation of radioactivity use in criminal offenses by forensic medicine is necessary. According to the Turkish Criminal law, the severity of destruction caused on the body by any agent carries importance in the decision making process by the court for final penalty. Homicide by chemical, biologic or nuclear weapons are considered to be purposeful homicide and punished with life sentence. In that regard, autopsy and post-mortem examinations can be requested from physicians to determine the cause of death after homicide cases in which radioactive material has been used. During the autopsy, additional safety precautions should be taken and continued during morgue and funeral processes. The methods of protection from radioactive material depend on the type of radiation and the half life of the agent. Therefore, radiation quantity should be measured prior to autopsy and a risk assessment should be made. When necessary, help needs to be requested from the radiation safety specialists. In this article, topics that need special attention during the post-mortem examinations of corpses that hold radioactivity are discussed.Key words: Radioactive elements, autopsy, safety, occupational health
Keywords: radioactive elements; autopsy; safety; occupational health